2015
DOI: 10.1111/nep.12425
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health Literacy and Kidney Function

Abstract: There is a small but significant association between HL and eGFR. Providers should use HL-tailored communication strategies in CKD patients. Larger multicentre studies are needed to substantiate this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 26 publications
2
61
1
2
Order By: Relevance
“…[1821]). Rates of limited health literacy in kidney disease range from 10 to 40% and have been associated with worse eGFRs in CKD, higher mortality rates in dialysis patients, and higher creatinine levels in transplant recipients and affect whether a patient is listed for or receives a transplant [2228]. To our knowledge, the effect of limited health literacy on immunosuppressant medication adherence in kidney recipients has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…[1821]). Rates of limited health literacy in kidney disease range from 10 to 40% and have been associated with worse eGFRs in CKD, higher mortality rates in dialysis patients, and higher creatinine levels in transplant recipients and affect whether a patient is listed for or receives a transplant [2228]. To our knowledge, the effect of limited health literacy on immunosuppressant medication adherence in kidney recipients has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Comfort with telehealth may also be influenced by familiarity and prior access to technology . Data have suggested that low health literacy and limited formal education are quite prevalent among individuals with CKD and ESRD, potentially limiting the efficacy of telehealth for optimal RRT education …”
Section: Examples Of Rrt Education Using Telehealthmentioning
confidence: 99%
“…In conclusion, previous research has shown that people with higher self-efficacy and adequate kidney knowledge have better self-management of adherence to medication regimens, partnership in health care, open communication, and kidney function compared to those with lower self-efficacy and inadequate kidney knowledge (Curtin et al, 2008;Devraj et al, 2015). Increased CKD self-management skills requires both a better understanding of kidney disease and confidence to manage the disease, which in turn, may prevent further deterioration of kidney function, and also to maintain their overall health and well-being.…”
Section: 41mentioning
confidence: 99%